Functional characterization of the catalytic and bromodomain of FgGCN5 in development, DON production and virulence of Fusarium graminearum - Qian-nan WANG; Pan-pan HUANG; Shan-yue ZHOU (Journal of Integrative Agriculture, 2020)
FgGCN5, a GCN5 homolog in Fusarium graminearum, plays a critical role in hyphal vegetative growth, asexual and sexual reproduction, deoxynivalenol (DON) biosynthesis and plant infection. For nuclear localized GCN5, four conserved sequence motifs (I–IV) are presented in the catalytic domain and a bromodomain in the carboxy-terminus. As a lysine acetyltransferase, conserved negatively charged residues are present to neutralize the protons from lysine substrates. However, the role of conserved motifs/domains and residues in FgGCN5 are unclear. Here, we generated deletion mutant strains for each the conserved motifs/domains and a glutamate residue 130 (E130) replacement mutant. Deletion of each conserved motif in the catalytic domain and replacement of E130 site resulted in manifold defects in hyphae growth, asexual and sexual development, DON biosynthesis, and plant infection. Phenotypic defects in the mutant strains were similar to deletion mutants. The deletion of the bromodomain led a significant reduction in DON production and virulence, with no effects on hyphae growth, asexual or sexual reproduction. FgGCN5 was further found to localize to the nucleus in conidia and hyphae cells. In conclusion, FgGCN5 encodes a nuclear localized acetyltransferase. The conserved motifs in the catalytic domain and E130 are essential for correct functions of the gene. The conserved bromodomain is important for DON production and pathogen virulence. This was the first report to identify the functions of conserved motifs/domains in FgGCN5, which will contribute to our understanding of the mechanism(s) by which FgGCN5 regulates F. graminearum.